ASCL1 promotes tumor progression through cell-autonomous signaling and immune modulation in a subset of lung adenocarcinoma. (1st October 2020) - Miyashita, Naoya; Horie, Masafumi; Mikami, Yu; Urushiyama, Hirokazu; Fukuda, Kensuke; Miyakawa, Kazuko; Matsuzaki, Hirotaka; Makita, Kosuke; Morishita, Yasuyuki; Harada, Hiroaki; Backman, Max; Lindskog, Cecilia; et al.
Abstract: The master regulator of neuroendocrine differentiation, achaete-scute complex homolog 1 (ASCL1) defines a subgroup of lung adenocarcinoma. However, the mechanistic role of ASCL1 in lung tumorigenesis and its relation to the immune microenvironment is principally unknown. Here, the immune landscape of ASCL1-positive lung adenocarcinomas was characterized by immunohistochemistry. Furthermore, ASCL1 was transduced in mouse lung adenocarcinoma cell lines and comparative RNA-sequencing and secretome analyses were performed. The effects of ASCL1 on tumorigenesis were explored in an orthotopic syngeneic transplantation model. ASCL1-positive lung adenocarcinomas revealed lower infiltration of CD8 +, CD4 +, CD20 +, and FOXP3 + lymphocytes and CD163 + macrophages indicating an immune desert phenotype. Ectopic ASCL1 upregulated cyclin transcript levels, stimulated cell proliferation, and enhanced tumor growth in mice. ASCL1 suppressed secretion of chemokines, including CCL20, CXCL2, CXCL10, and CXCL16, indicating effects on immune cell trafficking. In accordance with lower lymphocytes infiltration, ASCL1-positive lung adenocarcinomas demonstrated lower abundance of CXCR3-and CCR6-expressing cells. In conclusion, ASCL1 mediates its tumor-promoting effect not only through cell-autonomous signaling but also by modulating chemokine production and immune responses. These findings suggest that ASCL1-positive tumors represent a clinically relevant lung cancer entity. Graphical abstract: Image 1 Highlights: ASCL1-positive lung adenocarcinomas evoke minimal immune cell infiltration. ASCL1 promotes cell proliferation and tumorigenesis of lung adenocarcinoma cells. ASCL1 suppresses chemokine secretion from lung adenocarcinoma cells. ASCL1-positive lung adenocarcinomas show poor CXCR3-or CCR6-positive cell infiltration.